Utility of YouTube online learning for junior gastrointestinal endoscopists: A rewarding or deterring practice? - Mohamed, , Salem Youssef (2023)
Endoscopy is a competitive field in clinical practice, in which skilled endoscopists are in high demand. The learning process for Junior Gastrointestinal Endoscopists (JGEs) is difficult, quite long, and technically demanding. This directs JGEs to seek additive learning sources, including online sources. The purpose of this study was to determine the frequency, context, attitudes, perceived benefits, drawbacks, and recommendations for using YouTube videos as an educational platform among JGEs from the uses'prespective. We disseminated a cross-sectional online questionnaire from January 15th to March 17th, 2022, and recruited 166 JGE from 39 different countries. The majority of surveyed JGEs (138, 85.2%) were already using YouTube as a learning tool. The majority of JGEs (97, 59.8%) reported gaining knowledge and applying it in their clinical practice, but 56 (34.6 %) reported gaining knowledge without application in real practice. Most participants (124, 76.5 %) reported missing procedure details in YouTube endoscopy videos. The majority of JGEs (110, 80.9%) reported that YouTube videos are provided by endoscopy specialists. Only one participant, 0.6% out of the 166 JGEs surveyed, disliked video records, including YouTube as a source of learning. Based on their experience, 106 (65.4%) of participants recommended YouTube as an educational tool for the coming generation of JGEs. We consider that YouTube represents a potentially useful tool for JGEs, supplying them with both knowledge and clinical practice tricks. However, many drawbacks could make the experience misleading and time-consuming. Consequently, we encourage educational providers on YouTube and other platforms to upload well-constructed, peer-reviewed, interactive educational endoscopy videos.